Analisis Strategi Pemungutan Pajak Reklame Dalam Upaya Meningkatkan Pendapatan Daerah Di Badan Pengelola Keuangan Daerah Kota Tangerang Tahun 2020-2022 - Pratama, Rikardo; Fiatri, Lisa Arisa; Pribadi, Jiwa (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Billboard tax collection strategies are methods used to achieve targets in their realization. This study aims to identify several billboard tax collection strategies at the Regional Financial Management Agency of Tangerang City from 2020 to 2022. This research employs a descriptive qualitative method, with data collection techniques including observation, interviews, and documentation. The informants were selected using purposive sampling techniques and are experts in this field. The study results indicate that the strategies for billboard tax collection to increase regional revenue at the Regional Financial Management Agency of Tangerang City have not been maximized in their implementation, failing to meet the targets. The implementation process still encounters obstacles that affect the strategies for billboard tax collection. Several measures to optimize these strategies include sending reminders to billboard taxpayers about their obligations, providing educational socialization to taxpayers, improving the application to prevent errors, and ensuring proper maintenance.